Failure analysis of cerebral aneurysm - Mohd Yusrizal, Mohd Yusoof (2010)
The aneurysm is the abnormal bulging of a portion of an artery due weakness in the cerebral at the circle of Willis brain. Nowadays, cerebral aneurysm is the one of the disease which have killed the people very quickly. This occurs when the mechanical behavior exceeds the strength of the tissue. This study is focused on cerebral aneurysm. Investigations on the changes of flow phenomena and the mechanical behavior in cerebral aneurysm have been studied. By using the simulation tools, the stress behavior on this region has been analyzed. The normal size of cerebral diameter is about 3-7 mm and aneurysm can bulge and reach until 10 mm. The velocity profile, nodal pressure distribution, displacement of wall and the stress at the wall had been identified at locations of aneurysm. As the size of an aneurysm increases, there was a potential of rupture of aneurysm. This can result in severe hemorrhage or even worst, fatal event. The studies are proceed based on numerical approach. The result shown that mechanical behaviors inside aneurysm region would be different compare to the normal blood vessel. It was proved that the maximum velocity had been obtained is 0.192 m/s. The maximum displacement of wall aneurysm at the neck is 0.00005 mm and the maximum effective stress at the aneurysm is 21.70 MPa. For the pressure distribution, the highest pressure at the aneurysm is 15.6 KPa. This study would help to predict cerebral aneurysm and provide better understanding about the cerebral aneurysm.